Komunikasi Interpersonal Pendampingan Korban Kekerasan Seksual oleh Satuan Tugas Perlindungan Perempuan dan Anak Relawan Merah Putih Kabupaten Poso - Sari, Dyah Fitria Kartika; Wulandari, Dwi Rohma; Kudratullah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
This research describes interpersonal communication conducted by the PPA RMP task force in Poso Regency in the process of assisting victims of sexual violence. An interpersonal approach is one way to uncover sexual violence that occurs in society. Many cases do not continue and do not receive justice due to norms and fear of talking to others. By using qualitative research methods, as well as direct observation and interviews with informants supported by other field data, the results of this study describe interpersonal communication as playing a very important role during the assistance process, both psychologically, physically and legally. Maintaining stability and emotions, building trust with the victim's family and being professional by not showing empathy in front of the victim, are part of the interpersonal communication conducted by the sexual-violence victim's assistant at the PPA RMP in Poso Regency.